Resveratrol Enhances Cardiomyocyte Differentiation of Human Induced Pluripotent Stem Cells through Inhibiting Canonical WNT Signal Pathway and Enhancing Serum Response Factor-miR-1 Axis - Hui Liu; Shaoli Zhang; Lihua Zhao; Yan Zhang; Qiuping Li; Xiaoyan Chai; Yongchun Zhang (Stem Cells International)
Resveratrol (trans-3,5,4′-trihydroxystilbene) (RSV) is a natural polyphenol with protective effects over cardiac tissues and can affect cell survival and differentiation in cardiac stem cells transplantation. However, whether this agent can affect cardiomyocytes (CMs) differentiation of induced pluripotent stem cells (iPSCs) is not yet clear. This study explored whether RSV can affect CMs differentiation of human iPSCs. Under embryoid bodies (EBs) condition, the effect of RSV on the change of pluripotent markers, endoderm markers, mesoderm markers, and ectoderm markers was measured using qRT-PCR. Under CM differentiation culture, the effect of RSV on CM specific markers was also measured. The regulative role of RSV over canonical Wnt signal pathway and serum response factor- (SRF-) miR-1 axis and the functions of these two axes were further studied. Results showed that RSV had no effect on the self-renewal of human iPSCs but could promote mesoderm differentiation. Under CM differentiation culture, RSV could promote CM differentiation of human iPSCs through suppressing canonical Wnt signal pathway and enhancing SRF-miR-1 axis.